Association Between Smartphone Addiction and Functional Exercise Capacity in College Students - Manmeet Kaur Bhalla; Niraj Kumar; Deptee Warikoo (International Journal of Orthopedic Nursing and Practices, 2026)
Smartphone addiction has become increasingly prevalent among college students and is associated with various negative physical and psychological outcomes. Functional exercise capacity, a key indicator of physical fitness and health, may be adversely affected by excessive smartphone use due to sedentary behavior and reduced physical activity. This article examines the association between smartphone addiction and functional exercise capacity in college students by analysing behavioral, psychological, physiological, and methodological perspectives. Evidence suggests that higher levels of smartphone addiction are linked to decreased physical activity, poor cardiovascular endurance, and reduced functional performance. Psychological factors such as stress, anxiety, depression, and sleep disturbances further mediate this relationship. Intervention strategies including structured exercise programs, behavioral modification techniques, digital detox interventions, and wearable technology have shown promise in improving both smartphone use patterns and exercise capacity. The findings highlight the need for integrated health promotion strategies targeting both digital behavior and physical fitness among college populations.
Keywords: Exercise tolerance; Mental health; Sedentary behavior; Smartphone addiction Functional exercise capacity; college students; digital health; physical activity